The Predictive Ability of Administrative Empowerment and Narcissistic Leadership on Burnout among Faculty Members in Jordanian Universities - Shaqra, Rawan Kheder Abu; Alsadi, Mohammad (Journal of Ecohumanism, 2025)
This study aims to explore the predictive ability of administrative bullying and narcissistic leadership on burnout among faculty members in Jordanian universities. The descriptive correlational predictive method was used to analyze the relationship between these variables, focusing on the impact of administrative bullying and narcissistic leadership in predicting the level of burnout. The sample included 296 faculty members from Jordanian universities. The results showed that the studied variables had a low level of impact, yet there was a positive relationship between administrative bullying, narcissistic leadership, and burnout, suggesting that an increase in administrative bullying or narcissistic leadership could be associated with higher levels of burnout. The findings also indicated a predictive ability of administrative bullying and narcissistic leadership on burnout among faculty members in Jordanian universities. Based on these results, the study recommends improving the administrative and leadership environment in universities to reduce the impact of these factors on faculty well-being.